DAYA SAING PRODUK EKSPOR DI ERA PERDAGANGAN BEBAS - Suharsih, Sri; Sriwinarti, Asih (Jurnal Ekonomi & Studi Pembangunan, 2012)
Abstract: Efforts to improve the competitiveness of export products industry is one of the challenges faced by the Province of Yogyakarta in the era of trade liberalization. Therefore this study aims to determine the potential and competitiveness of export products Yogyakarta province. By using the analysis Location Quotient (LQ), Yogyakarta Province has six subbase in the industrial sector of food beverages and tobacco industry, textile industry, leather goods and footwear, manufacture of wood and other products of wood, paper and printing industry, manufacture of cement and non-metal mineral goods and other goods industry. Based on Shift Share analysis, industry sectors that have the largest share of growth in the DIY PDRB is the food industry sub-sectors, textiles and leather goods, and craft industries. While it is based on the analysis Comparative Revealed Advantage (RCA) and the specialization index, known to export products that have good prospects for the future and is highly competitive Tanning and dressing of leather, wood and products of wood and woven goods, and textile and textile goods.Abstrak: Upaya peningkatan daya saing industri produk ekspor merupakan salah satu tantangan yang harus dihadapi oleh Provinsi Yogyakarta dalam era Liberalisasi Perdagangan. Penelitian ini bertujuan mengetahui potensi dan daya saing produk ekspor Provinsi Yogyakarta. Dengan menggunakan analisis Location Quotient (LQ) Provinsi Yogyakarta mempunyai enam subsektor basis pada sektor industri yaitu industri makanan minuman dan tembakau, industri tekstil, barang dari kulit dan alas kaki, industri kayu dan barang dari kayu lainnya, industri kertas dan barang cetakan, industri semen dan barang galian bukan logam, serta industri barang lainnya. Berdasarkan analisis Shift Share, sektor industri yang mempunyai pangsa terbesar bagi pertumbuhan PDRB di Yogyakarta adalah subsektor industri makanan, tekstil dan barang dari kulit, serta industri kerajinan. Sementara itu berdasarkan analisis Revealed Comparatif Advantage (RCA) dan Indeks Spesialisasi, diketahui produk ekspor yang mempunyai prospek baik di masa datang dan berdaya saing tinggi adalah kulit dan barang dari kulit, kayu, barang dari kayu dan barang anyaman, serta tekstil dan barang dari tekstil.Â